Religious practices in trauma coping - Khairil Razali (Indonesian Journal of Islam and Muslim Societies, 2013)
Disasters happen in Indonesia current days bring the country into a very disaster- prone country in the Ring of Fire cataclysm. Mega event devastating 2004 tsu- nami in Aceh Province and Nias have serious consequences for vulnerable groups of parents and children. This paper examines the presence of children in any catastrophic events, especially related to the psychological impact as well as adequate treatments to reduce and eliminate the prolonged psychological trauma. The 2004 tsunami in Aceh and a number of other natural catastrophic disasters have strengthened the effects of traumatic for children in Aceh and elsewhere in Indonesia. A series of earthquakes has built a-sustainable traumatic attitudes within children. This qualitative study learned from children from children cen- ters in Aceh towards their coping strategies and roles of religious practices. In conclusion that it should be a concern to establish social support systems for children to lessen the impact in the future.